Aid Volatility and Real Business Cycles in a Developing Open Economy. - Houndonougbo, Ahiteme N. (Southern Economic Journal, 2017)
This article analyzes the impact of the unpredictability of foreign aid on macroeconomic fluctuations in the recipient country. I build a small open-economy business cycle model that accounts for foreign aid shocks, with no preference shocks. The model is calibrated to reflect the structural empirical regularities of Cote d'Ivoire, a typical aid-dependent developing country. The parameters of the exogenous shocks are estimated using Bayesian methods and time series data for Cote d'Ivoire. The model produces business cycle patterns that are consistent with the data and key stylized facts. Specifically, the excess volatility of consumption with respect to output is successfully replicated. The results suggest that the unpredictability of foreign aid contributes to explain the volatility of business cycles in the recipient economy and has negative welfare effects.